LCL Model Experiential Learning based Training Model Development to Improve Teacher Competence in Designing Learning - Nirtha, Eva Nirtha; Ismanto, Bambang Ismanto; Sulasmono, Bambang Suteng (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Teacher’s competence in designing learning is one of the important aspects in getting the success of education. Based on preliminary research, any teacher didn’t make a learning design in teaching. Professional teacher certainly has variety experiences. However, experience-based training has rarely been given for the professional teacher. This research aimed to produce and determine the effectiveness the LCL model-based Experiential Learning training model to improve teacher competence in designing learning. It was developed based on Borg and Gall R&D model, carried out until the seventh stage using qualitative and quantitative approaches. The average validity score is 82.5 categorized as highly deserving by validators. ANCOVA's test results showed that there is a significant difference between classes, with the value of [F= (1,58), D=83,29, ρ=0.000, ƞρ2=0,58] significance value ρ=0.05. Based on the LSD table, the average corrected value of the treatment group was 72.84, while the control group was 45.69. It concluded that the training model is feasible and effectively used. This training model can be used as an alternative training to improve teacher competence, especially in designing learning that meets the elements of the 21st century learning paradigm and it has been completed by training tools such as module, guides and necessary hands-out.